Comparative Analysis of Railway Transport to the Voivodship Centers of Eastern Poland — Cities of Białystok, Lublin, and Rzeszów - Sławomir Goliszek; Marcin Połom (Barometr Regionalny)
The article presents and compares railway transport to various voivodship centers of Eastern Poland which vary in terms of spatial resistance. Spatial resistance, which depends on many factors such as railway and stock infrastructure, has a major impact on the lengthening or shortening of travel time, distances and costs. Presentation of data and comparison of individual centers provides grounds for developing a strategy for further development. Availability of railway access is illustrated with several result maps. Maps depict the three most important elements related to covering distances by train. Factors analyzed include: travel time (isochrone), distance by rail and the cost of travel (isodapane) to the voivodship centers of Eastern Poland. Graphic studies provide data for the calculations presented in the charts subject to analysis. In summary, the article shows which voivodship centers of Eastern Poland feature better railway transport accessibility.